Šlechtičny z rodu Dalbergů a silva rerum 2. poloviny 19. století - Dana Marešová (Theatrum Historiae)
Kunigunda (1827–1892) and Karolina (1874–1935) von Dalberg owned the books and they wrote about their thoughts into them. These books have been stored in the chateau of Dačice and they were forgotten for a long period of time. It was really difficult to classify them due to their complicated structure. I was able to categorize them amongst the ego-documents and I found out they corresponded to the sources called silva rerum. It is very difficult to define this type of a source, because it consists of a miscellaneous content (poems, alba amicorum and diaries entries, pictures, photos etc). What is also special about them is the fact they are quite rare in our area, and that is why just a little of research has been done so far. It is a source of a personal nature and it offers a lot of information. In future, it can also provide answers to various questions related to a personal and public life, everydayness, the way of thinking, the contacts network and many others from the aristocratic life of the 19th century.